PENGARUH TEKNOLOGI INFORMASI, TEKNIK AUDIT, TEKANAN ANGGARAN WAKTU TERHADAP KUALITAS HASIL AUDIT - Murfadila Murfadila; Muhammad Reza Ramdani (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
This research examines the effect of information technology, the application of audit techniques and time budget pressures on the quality of audit results at KAP offices in Makassar. The research objective was to see the level of influence of information technology, the application of audit techniques and time budget pressures on the quality of audit results. The study was conducted at 9 KAP offices in Makassar, 40 Auditor's research samples. Data collection techniques were carried out with a questionnaire with a scale value of 5. Data analysis using multiple regression analysis. From the results of information technology research has a positive and significant effect on the quality of audit results. the application of audit techniques has a positive and significant effect on the quality of audit results. time budget pressure has a positive and significant effect on the quality of audit results.